A Comparative Study on Cultural Industry Investment and Financing in China and The United States - Lian, Haobo (Transactions on Economics, Business and Management Research, 2024)
The paper examines the investment and financing strategies employed in the cultural industries of China and the United States. By analyzing the regulatory frameworks, funding sources, and financial processes in each country, we aim to uncover the challenges and opportunities facing the cultural sector. The comparative analysis reveals key insights that can inform future development in both regions. The cultural industries in China and the United States are integral to their economies, contributing significantly to GDP and employment. The governments of both countries have prioritized investment and support for the cultural sector, launching programs aimed at fostering cultural exchange, developing creative enterprises, and preserving cultural heritage. However, differences in regulatory frameworks, funding sources, and investment patterns can impact the competitiveness and sustainability of cultural enterprises. This study seeks to provide a comparative analysis of investment and financing in the cultural industries of China and the United States to shed light on the distinct tactics and techniques used to promote cultural development.